Sampled-data observer design for sensorless control of wind energy conversion system with PMSG - Zaggaf, Mohammed Hicham; Mansouri, Adil; El Magri, Abdelmounime; Watil, Aziz; Lajouad, Rachid; Bahatti, Lhoussain (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
This paper presents a nonlinear observer for a variable-speed wind energy conversion system (WECS) utilizing a permanent magnet synchronous generator (PMSG). The study addresses the design of high-gain sampled-data observers based on the nonlinear WECS model, supported by formal convergence analysis. An essential aspect of this observer design is the incorporation of a time-varying gain, significantly enhancing system performance. Convergence of estimation errors is demonstrated using the input-to-state stability method. Simulation of the proposed observer is conducted using the MATLAB-Simulink tool. The obtained results are presented and analyzed to showcase the overall effectiveness of the proposed system.